Ultrasound Assisted Methods for Enhanced Extraction of Phenolic Acids from Quercus Infectoria Galls - Rohayu, Jusoh; Nuramira Fateha, Sukor; Nur Syahirah, Kamarudin (Elsevier Ltd, 2018)
Quercus Infectoria galls or known as Manjakani, is one of the potential herbs that have multiple therapeutic properties and are widely used in folklore medicine. Phenolic acids, including gallic acid and tannic acid, have been extracted from the galls by using different ultrasound extraction system (probe-type and bath-type) and the results were compared with the conventional extraction system. The effect of sonication time, solvent types and solvent concentration on the extraction yield of the phenolic acids has been investigated. The maximum extraction yield obtained for gallic acid and tannic acid are 2155.77 mg/kg and 15236.83 mg/kg, respectively in 8 h extraction time, operating temperature of 70°C, solid to solvent ratio of 1:10, ultrasonic power of 11 W and ultrasound frequency of 20 kHz with 0.1 M hexadecyltrimethylammonium bromide as the solvent. The obtained yield was significantly higher as compared to the conventional extraction system where only about 794.57 mg/kg yield was achieved. Peleg’s model was used to describe the kinetics of probe-type ultrasound extraction system and the model showed a good agreement with the experimental results. Therefore, it can be concluded that probe sonication system significantly induces the extraction efficiency to increase the bioactive constituents yield.